2012
DOI: 10.1002/acr.20683
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the epidemiology of systemic lupus erythematosus in the Asia‐Pacific region: Prevalence, incidence, clinical features, and mortality

Abstract: Objective. Systemic lupus erythematosus (SLE), a chronic multisystem autoimmune disease with a wide spectrum of manifestations, shows considerable variation across the globe, although there is little evidence to indicate its relative prevalence in Asia. This review describes its prevalence, severity, and outcome across countries in the Asia-Pacific region. Methods. We conducted a systematic literature search using 3 groups of terms (SLE, epidemiology, and Asia-Pacific countries) of EMBase and PubMed databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
238
3
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(274 citation statements)
references
References 36 publications
14
238
3
19
Order By: Relevance
“…3 Studies have also demonstrated that the prognosis of SLE is worse in nonwhite persons, in whom there is a younger age at onset of their disease, as well as a higher frequency of severe renal disease. [1][2][3][4][5] These observations may be due to 'protective factors' associated with European ancestry or may indicate the presence of specific risk factors associated with other ethnic groups. Based on these aforementioned findings, it may be argued that persons of non-European ancestry diagnosed with SLE should be more closely monitored.…”
Section: Lupus Erythematosusmentioning
confidence: 96%
See 1 more Smart Citation
“…3 Studies have also demonstrated that the prognosis of SLE is worse in nonwhite persons, in whom there is a younger age at onset of their disease, as well as a higher frequency of severe renal disease. [1][2][3][4][5] These observations may be due to 'protective factors' associated with European ancestry or may indicate the presence of specific risk factors associated with other ethnic groups. Based on these aforementioned findings, it may be argued that persons of non-European ancestry diagnosed with SLE should be more closely monitored.…”
Section: Lupus Erythematosusmentioning
confidence: 96%
“…Based on these aforementioned findings, it may be argued that persons of non-European ancestry diagnosed with SLE should be more closely monitored. 4,5 Caution should be excised with this approach given that all affected individuals do still have the risk of developing severe complications of their disease. There are other phenotypic characteristics that may vary in relation to ethnicity.…”
Section: Lupus Erythematosusmentioning
confidence: 99%
“…LE suffered more by women than men especially during reproductive period Advances in Health Science Research, volume 8 [12]. Life expectancy increased over the last 5 years in Asia Pacific countries, 60% Australia, 94% South Korea, 97% Hong Kong, 98% China (Shanghai), whereas in the last 10 years 70% of Malaysia, and 94% of Hongkong [15]. High mortality rates in men versus women due to cardiovascular disorders resulting from the habit of smoking [12].…”
Section: Case Reportmentioning
confidence: 99%
“…Many studies (epidemiological) have found that Caucasians have a twofold to threefold lower incidence and prevalence rates than Asians [72][73][74][75][76][77][78][79]. Moreover, it was found in many studies that Asians had more severe symptoms and signs of the disease, more aggressive kidney involvements, and the autoantibody positivity was also higher in Asians than in non-Asians [76,[79][80][81][82][83].…”
Section: Incidence and Prevalence Of Slementioning
confidence: 99%